KARAKTERISASI KERAGAMAN GENETIK 27 GENOTIPE CABAI BERDASARKAN MARKA SSR (SIMPLE SEQUENCE REPEAT) - Rerenstradika Tizar Terryana; Kristianto Nugroho; Habib Rijzaani; Puji Lestari (BERITA BIOLOGI, 2018)
Chili pepper (Capsicum annuum) is one of the high economical horticultural comodity in Indonesia and its genetic diversity contributes to the success of breeding programs. Simple sequence repeat (SSR) markers can be used to analyze genetic diversity among chili pepper genotypes. The aim of this research was to analyze the genetic diversity of twenty-seven genotypes of chili pepper by using 24 SSR markers. The collected data was analyzed using cluster analysis and principle coordinate analysis (PCoA). The result showed that high allele variation (4–17 alleles) was observed among chili pepper genotypes tested, with an average allele number and Polymorphism Information Content (PIC) value was 7.708 and 0.758 (0.598–0.920) respectively. All of SSR markers showed PIC value >0.5 which indicated that these markers were suitable for chili pepper diversity studies with a high differentiation and with the average value of genetic diversity was 0.78. The clustering and principle coordinate analysis showed that twenty-seven genotypes of chili pepper were divided into two groups (coefficient of similarity 0.74 in cluster analysis) indicating a high genetic variability among them. Genetic diversity analysis in this study will be useful as an initial basis of selection for appropriate parents with desired traits to assist the breeding program of chili pepper in Indonesia.